(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The concept of an economic zone emerged in international relations at the beginning of the 70s. The right to establish 200 miles’ exclusive economic zone was very quickly accepted, however the discussion concerning its legal content, scope of rights and obligations of third states was carried on .almost until the end of the HI Conference. As a result of prolonged negotiations art. 55 of the convention of 1982 was adopted which says that an exclusive economic zone is the territory outside the territorial sea and the adjoining area It is also not a part of open sea and has a special legal status (suii generis) defined by the provisions of the convention. The essence of it is that, on the one hand, waterside states enjoy sovereign rights there, on the other hand, third states also enjoy rights resulting from the fact that in the field of freedom of communication the economic zone is a territory where the prinCiple of freedom of seas is binding and where the provisions on open sea formulated in art. art. 88 to 115 are applied. Thus the pro-visions on open sea regulate and are a constituent part of legal status of the eco-nomic zone. Land-locked states and those unfavourably geographically situated (art. 69 and 70) have a right to participate in the exploitation of surplus living resour-ces of the economic zone of waterside states of the same region or subregion. The fact that the economic zone has been generally established justifies the thesis that at present the right to establish it and observe freedom of communication there may be considered an international custom. However, this cannot be stated in. view of the lack of uniformity of international practice concerning special provisions which define its legal status.